2003
DOI: 10.1093/nar/gkg545
|View full text |Cite
|
Sign up to set email alerts
|

ELM server: a new resource for investigating short functional sites in modular eukaryotic proteins

Abstract: Multidomain proteins predominate in eukaryotic proteomes. Individual functions assigned to different sequence segments combine to create a complex function for the whole protein. While on-line resources are available for revealing globular domains in sequences, there has hitherto been no comprehensive collection of small functional sites/motifs comparable to the globular domain resources, yet these are as important for the function of multidomain proteins. Short linear peptide motifs are used for cell compartm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
553
0
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 559 publications
(561 citation statements)
references
References 41 publications
4
553
0
4
Order By: Relevance
“…Idas orthologues in mouse (LOC622408) and Xenopus laevis (LOC100158359) were identified by Blast using the human Idas protein sequence as query. For sequence analysis and alignments, the following programs were used: Gene2EST (24), Coils (25), ELM (Eukaryotic Linear Motif) resource for functional sites in proteins (26), and ClustalW (27).…”
Section: Methodsmentioning
confidence: 99%
“…Idas orthologues in mouse (LOC622408) and Xenopus laevis (LOC100158359) were identified by Blast using the human Idas protein sequence as query. For sequence analysis and alignments, the following programs were used: Gene2EST (24), Coils (25), ELM (Eukaryotic Linear Motif) resource for functional sites in proteins (26), and ClustalW (27).…”
Section: Methodsmentioning
confidence: 99%
“…We first review how genetic lesions can lead to altered protein function, which can result in changes to the structure and p e r s p e c t i v e npg An insightful example of how to explore this sequence-function relationship in protein domains was carried out by researchers in the Ranganathan and Yaffe laboratories who, using methods from statistical mechanics, generated synthetic WW domains de novo that maintained fold and function 17,18 . Further supporting a complex sequencefunction relationship, additional studies from the Ranganathan laboratory demonstrated that, in addition to protein architecture described as combinations of modules such as globular domains and linear motifs [19][20][21] , protein domains themselves often have welldefined sectors formed by sparse networks of residues often linking spatially distant regions that contribute cooperatively but unequally to its function 22,23 . Although some targeted studies analyzing several cancer mutations in a single kinase have been conducted 24 , similar approaches to those used for WW domains should be pursued to generate high-throughput experimental studies of cancer mutations in the context of signaling networks.…”
Section: From Genomic Lesions To Functional Network Perturbationsmentioning
confidence: 99%
“…ELM (http://elm.eu.org) 19 and ProP 1.0 (http:// www.cbs.dtu.dk) 20 algorithms predicted the existence of a furin consensus cleavage site (R 332 NRR 335 2) at position 335, which is conserved among human, mouse ( Figure 1A), and rat. The furin cleavage site is present also in zebrafish HJV, although at different position.…”
Section: A Specific Furin Cleavage Site Of Hjvmentioning
confidence: 99%